Myofibrillar protein accumulation but reduced protein synthesis in PDCD4-depleted myotubes - Stephen Mora; Lilia Alihemmat; Logan D. Davari; Termeh Ataie; Parsa Nafari Mehranjani; Luke Flewwelling; Arthur J. Cheng; Olasunkanmi A. J. Adegoke (PLoS ONE, 2026)
Skeletal muscle is critical to whole-body functionality and homeostasis. The mammalian/mechanistic target of rapamycin complex 1 (mTORC1) is a nutrient/growth-factor sensitive positive regulator of skeletal muscle mass. Amongst other substrates, mTORC1 phosphorylates the ribosomal protein S6 kinase (S6K1). Activated S6K1 acts through multiple effectors, including programmed cell death 4 (PDCD4), to promote mRNA translation and protein synthesis. Much of what is known about PDCD4 is in non-muscle cells. We previously demonstrated that the effect of PDCD4 differs between myoblasts and myotubes. Here, we showed that PDCD4 depletion in myotubes enhanced myotube diameter (+36%) and accumulation of myofibrillar proteins (+163–237%). These effects occurred along with increased phosphorylation of AKT ser473 (+85%) and of the mTORC1 substrate S6K1 thr389 (+152%), but protein synthesis was suppressed. There was increased phosphorylation of FoxO3a ser253 (+250%) and a corresponding reduction in the expression of the muscle protein ubiquitin ligase MuRF1 (–44%), but there was no significant effect on measures of proteolysis or autophagy. In starved myotubes treated with the proteasome inhibitor MG132, accumulation of ubiquitinated proteins was attenuated in PDCD4-depleted cells. PDCD4 depletion did not augment sarcoplasmic reticulum (SR) Ca 2+ release capacity but was associated with reduced ATP and intracellular amino acid levels. Finally, AKT inhibition partially attenuated the effect of PDCD4 depletion on myofibrillar protein abundance. In summary, myofibrillar protein accumulation in PDCD4-depleted myotubes did not lead to improved intracellular Ca 2+ handling, likely due to reduced energy level. Our data point to a pivotal role for PDCD4 in regulating myotube size.